Lessing’s Influence on the Development of Mendelssohn’s Theory of Mixed Sentiments - Genazzano, Pablo (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This article investigates the influence of Lessing on Mendelssohn’s theory of mixed sentiments. It takes as its point of departure Lessing’s letter to Mendelssohn of 2 February 1757, which proposes that all passions, even unpleasant ones, can ultimately give rise to pleasure by making the soul aware of its own representational activity. The article first situates this principle in relation to Mendelssohn’s standpoint in On Sentiments (1755). It then shows how Mendelssohn adapted Lessing’s insight in his engagement with Burke, especially in response to the paradox of deriving pleasure from the misfortune of others. The analysis follows Mendelssohn’s reception of Burke in the 1761 edition of the Rhapsody, and culminates in its 1771 edition, where he reformulates Lessing’s principle to ground a more universal source of pleasure: not in the object itself, but in the soul’s reflection on its own representational powers